2009
DOI: 10.1186/1471-2458-9-139
|View full text |Cite
|
Sign up to set email alerts
|

Use of television, videogames, and computer among children and adolescents in Italy

Abstract: Background: This survey determined the practices about television (video inclusive), videogames, and computer use in children and adolescents in Italy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
35
1
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 26 publications
9
35
1
8
Order By: Relevance
“…The Australian Department of Health and Ageing (ADHA), and other international authorities such as the American Academy of Paediatrics (AAP), recommend that children and adolescents should not spend more than two hours per day viewing TV [31,42]. Based on this recommendation, only 25% of male and 22% of female participants in this study met the recommendation of less than or equal to 2 hours of watching TV.…”
Section: Screen Timementioning
confidence: 65%
“…The Australian Department of Health and Ageing (ADHA), and other international authorities such as the American Academy of Paediatrics (AAP), recommend that children and adolescents should not spend more than two hours per day viewing TV [31,42]. Based on this recommendation, only 25% of male and 22% of female participants in this study met the recommendation of less than or equal to 2 hours of watching TV.…”
Section: Screen Timementioning
confidence: 65%
“…Although results regarding the influence of age on time spent watching TV are contradictory, by contrast, almost all the aforementioned studies showed that boys usually spend more time watching TV than girls 6,14,15,16,17,18,19,20,21,22 .…”
Section: Discussionmentioning
confidence: 86%
“…The level of internet use for non-study reasons in previous studies is generally low. In some cases no differentiation was made between internet use for non-study and study reasons 27 and in general internet use is included in the category computer use 15,17,18,20,22,24 .…”
Section: Discussionmentioning
confidence: 99%
“…Generally, adolescents that belong to a less favoured social class presented higher levels of media use 1,16,26,27 . A similar pattern was found among adolescents with younger and older parents, as well as those that did not live with both parents.…”
Section: Discussionmentioning
confidence: 99%